Top wealth and its historical origins: An analysis of Germany's largest privately held fortunes in 2019 - Daria Tisch; Emma Ischinsky (Max Planck Institute for the Study of Societies, 2023)
Rising wealth inequality is both a topic in recent policy discussion and in the social sciences. Despite the general interest in wealth concentration, we know only little about the largest privately held fortunes. To help fill this gap we analyze the historical origins of Germany's 1,032 largest fortunes in 2019. In particular, we identify the share of entrenched fortunes - fortunes which date back to the beginning of the twentieth century - and ask to what extent they differ from more recently established ones. Furthermore, we examine in an exploratory way if entrenched fortunes are connected to fortunes with more recent origins through family lines. We use a journalistic rich list published by the manager magazin in 2019, which we link with both rich lists from 1912/1914 and Wikidata. We find that about eight percent of today's fortunes can be traced back to fortunes held by the same families in 1913. Regression analyses show that entrenched fortunes rank on average higher on the rich list than the remaining ones. Descriptive network analyses indicate that some of today's largest fortunes are intertwined through marital lines, hinting at social closure at the top. Our findings indicate that the accumulation and perpetuation of fortunes over many generations is an important feature of top wealth in Germany. – – Die zunehmende Vermögensungleichheit wird sowohl in aktuellen politischen Debatten als auch in den Sozialwissenschaften diskutiert. Trotz des breiten Interesses an der Vermögenskonzentration wissen wir bislang jedoch nur wenig über die größten Privatvermögen. Daher untersuchen wir die historischen Ursprünge der 1.032 größten deutschen Vermögen des Jahres 2019. Wir ermitteln zunächst den Anteil der verwurzelten Vermögen - Vermögen, die auf den Beginn des 20. Jahrhunderts zurückgehen - und fragen, inwieweit sie sich von jüngeren Vermögen unterscheiden. Außerdem untersuchen wir explorativ, ob verwurzelte Vermögen durch Familienlinien mit jüngeren Vermögen verbunden sind. Dazu greifen wir auf eine journalistische Reichenliste des manager magazins aus dem Jahr 2019 zurück, die wir sowohl mit Reichenlisten aus den Jahren 1912/1914 als auch mit Wikidata verknüpfen. Wir zeigen, dass etwa acht Prozent der heutigen Vermögen auf Vermögen zurückgehen, die dieselben Familien bereits 1913 besessen haben. Die Regressionsanalysen zeigen, dass verwurzelte Vermögen durchschnittlich höher auf der Reichenliste rangieren als die übrigen Vermögen. Deskriptive Netzwerkanalysen weisen darauf hin, dass einige der größten Vermögen von heute durch Eheschließungen miteinander verbunden sind, was auf eine soziale Schließung an der Spitze der Vermögensverteilung hindeutet. Unsere Ergebnisse zeigen, dass die Akkumulation und die Aufrechterhaltung von Vermögen über Generationen hinweg wichtige Merkmale des deutschen Spitzenvermögens sind.
hdl:21.11116/0000-000D-048A-3
Keywords: 300; elite; family; inheritance; network analysis; super-rich; wealth perpetuation; Elite; Erbschaft; Familie; Netzwerkanalyse; Reichtum; Vermögen